The effect of baricitinib on pSTAT3 levels in IL-6- or IL-15-stimulated PBMCs isolated from patients with SLE - Szebeni, Gábor J.; Gémes, Nikolett; Neuperger, Patrícia; Szabó, Enikő; Balog, József Á.; Honfi, Dániel; Balog, Attila; Toldi, Gergely (Frontiers in Immunology, 2025)
IntroductionSystemic lupus erythematosus (SLE) is a systemic autoimmune disease marked by multi-organ inflammation. Its pathogenesis involves profound T-cell dysfunction, autoreactive B-cell activation, impaired CD8+ T-cell responses, myeloid cell abnormalities, and dysregulated cytokine secretion. Central to cytokine-driven immune activation is the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway. Baricitinib, a selective oral JAK1/2 inhibitor approved for rheumatoid arthritis, has been extensively studied in SLE. MethodsWe aimed to investigate STAT3 phosphorylation in CD4+ and CD8+ T cells and CD11b+ myeloid cells from patients with SLE using single-cell flow cytometry of peripheral blood mononuclear cells (PBMCs) stimulated ex vivo with interleukin-6 (IL-6) or IL-15. We quantified pSTAT3 induction and assessed the inhibitory effect of baricitinib. ResultsDespite long-term immunomodulators, significant STAT3 activation was observed in T cells and myeloid cells upon IL-6 or IL-15 stimulation in patients with SLE. Baricitinib effectively inhibited STAT3 phosphorylation in these cell types, though its inhibitory effect was notably weaker following IL-15 stimulation compared to IL-6. Notably, baricitinib did not affect the proportion of interferon-γ (IFN-γ)- or IL-17-expressing cells. ConclusionThese findings highlight the cell-type and cytokine-specific effects of baricitinib and demonstrate its capacity to dampen IL-6- and IL-15-mediated STAT3 activation in key immune cell subsets. Our results support a precision medicine approach to JAK inhibition in SLE and reinforce the potential of baricitinib in modulating key inflammatory pathways.